Sticking for a Cause: The Falciparum Malaria Parasites Cytoadherence Paradigm - Lee, Wenn-Chyau; Russell, Bruce; Rénia, Laurent (Frontiers in Immunology, 2019)
After a successful invasion, malaria parasite Plasmodium falciparum extensively remodels the infected erythrocyte cellular architecture, conferring cytoadhesive properties to the infected erythrocytes. Cytoadherence plays a central role in the parasite’s immune-escape mechanism, at the same time contributing to the pathogenesis of severe falciparum malaria. In this review, we discuss the cytoadhesive interactions between P. falciparum infected erythrocytes and various host cell types, and how these events are linked to malaria pathogenesis. We also highlight the limitations faced by studies attempting to correlate diversity in parasite ligands and host receptors with the development of severe malaria.